2014
DOI: 10.2196/resprot.2776
|View full text |Cite
|
Sign up to set email alerts
|

Examining Participant Engagement in an Information Technology-Based Physical Activity and Nutrition Intervention for Men: The Manup Randomized Controlled Trial

Abstract: BackgroundMales experience a shorter life expectancy and higher rates of chronic diseases compared to their female counterparts. To improve health outcomes among males, interventions specifically developed for males that target their health behaviors are needed. Information technology (IT)-based interventions may be a promising intervention approach in this population group, however, little is known about how to maximize engagement and retention in Web-based programs.ObjectiveThe current study sought to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…4 Process evaluation showed that engagement was high during the first intervention phase (i.e., including the CHOICES course and initial months of website utilization). 40 However, consistent with other trials using similar intervention platforms, 41-43 engagement declined thereafter. After the first 4 months of the intervention, process results indicate that 30-40% of participants continued to engage in the CHOICES website.…”
Section: Discussionsupporting
confidence: 87%
“…4 Process evaluation showed that engagement was high during the first intervention phase (i.e., including the CHOICES course and initial months of website utilization). 40 However, consistent with other trials using similar intervention platforms, 41-43 engagement declined thereafter. After the first 4 months of the intervention, process results indicate that 30-40% of participants continued to engage in the CHOICES website.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to other Internet-based PA programs [22,28,42,45]. Most participants felt that the information provided was useful and relevant and they indicated that they were more aware of their level of daily activity.…”
Section: Discussionsupporting
confidence: 72%
“…Our results suggest that mobile devices might be an effective way to reach men, as the majority of our sample reported that they use a smartphone. The accessibility and interactive nature of mobile technology may enhance men's engagement with health interventions (Short et al, 2014). Therefore, future initiatives to increase men's knowledge should capitalize on emerging technologies, such as mobile health applications, to educate men about their own fertility.…”
Section: Discussionmentioning
confidence: 99%